Cross-counterflow heat exchanger assembly - SMITH GREGORY RONALD; CORSER DON CLAIR; ODDI FREDERICK VINCENT (2010)
This invention relates to a cross-counterflow heat exchanger assembly. Disclosed is a manifold which use in a heat exchanger assembly (20) and a method of forming the manifold is disclosed herein. Themethod starts with the step of separately forming a first member (22) at least partially defining an interior and having a spaced set of first tube slots (30) and a second member (32) having a wall (36) positioned against the first tube slots (30) and dividing the interior into a plurality of chambers (38, 40). The method is finalized with the step of permanently fixing the first member (22) to the second member (32) to define an first manifold (42) after the separately forming step.